High-transparency PE / PA asymmetric film and preparation method thereof

By using the interlayer structure of PA/TIE/LLD/LLD/LD/TIE/PA/TIE/LLD in the PE/PA asymmetric membrane and the reasonable ratio of PE and PA, the transparency problem caused by microcrystals in traditional membranes is solved, and high transparency and multiple performance improvements are achieved.

CN119567683APending Publication Date: 2025-03-07SHANGHAI TANGKE NEW PACKAGING CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411744112.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-30
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

In traditional PE/PA asymmetric films, PA is prone to form microcrystals, resulting in light scattering, reducing the transparency of the film, and affecting its performance in high-end packaging and optical applications.

Method used

The interlayer structure of PA/TIE/LLD/LLD/LD/TIE/PA/TIE/LLD is adopted. By reasonably proportioning PE and PA, the TIE layer is used as the bonding layer to enhance the adhesion between polymer layers, reduce interlayer peeling, and thereby improve the transparency of the film.

Benefits of technology

High optical transparency is achieved, the PA layer has excellent density, chemical resistance and heat resistance, the PE layer has excellent mechanical strength, stability and transparency, and the prepared PE/PA asymmetric film has good transparency, chemical stability, heat resistance and mechanical strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005163221900000101
    Figure BDA0005163221900000101
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer materials, and particularly discloses a high-transparency PE / PA asymmetric film and a preparation method thereof. The structure of the high-transparency PE / PA asymmetric film is PA / TIE / LLD / LLD / LD / TIE / PA / LLD, and the weight ratio between layers of the high-transparency PE / PA asymmetric film is (0.125 to 0.131): (0.064 to 0.070): (0.073 to 0.079): (0.073 to 0.079): (0.218 to 0.224): (0.064 to 0.070): (0.103 to 0.109): (0.064 to 0.070): (0.189 to 0.195). According to the present invention, through the reasonable ratio of PE to PA, the high optical transparency of the film is achieved, and the prepared PE / PA asymmetric film has advantages of good transparency, good chemical stability, good heat resistance and good mechanical strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of polymer materials, and in particular to a highly transparent PE / PA asymmetric film and a preparation method thereof. Background Art

[0002] PE / PA membrane refers to a membrane material composed of polyethylene (PE) and polyamide (PA, also known as nylon). It can be divided into two categories according to its structural characteristics: symmetric membrane and asymmetric membrane. The structure of a symmetric membrane is symmetrical, such as a structure with PA in the middle layer and PE on both sides. The structural feature of an asymmetric membrane is asymmetry, such as a seven-layer co-extruded nylon membrane with an asymmetric structure of PE / TIE / PE / PA / PE / TIE / PA.

[0003] Among PE / PA asymmetric films, due to its good physical properties and processing performance, it has been widely used in the packaging and optical industries. PE / PA asymmetric film is a film co-extruded from different plastic materials. It has the characteristics of high barrier, oil resistance, moisture resistance, high temperature cooking resistance, low temperature freezing resistance, etc. It is suitable for the packaging of food, industrial and medical products. Its basic structure is PE / TIE / PE / PA / TIE / PE / PA, and the thickness ranges from 0.35-0.50mm.

[0004] In traditional PE / PA asymmetric films, PA easily forms microcrystals. These microcrystal structures scatter light, thereby reducing the transparency of the film and affecting its performance in high-end packaging and optical applications. Summary of the invention

[0005] In order to improve the problem of poor transparency of PE / PA asymmetric films, the present application provides a highly transparent PE / PA asymmetric film and a preparation method thereof.

[0006] The present application provides a highly transparent PE / PA asymmetric film, which adopts the following technical solution: A highly transparent PE / PA asymmetric film has a structure of PA / TIE / LLD / LLD / LD / TIE / PA / TIE / LLD, and an interlayer weight ratio of 0.125-0.131:0.064-0.070:0.073-0.079:0.073-0.079:0.218-0.224:0.064-0.070:0.103-0.109:0.064-0.070:0.189-0.195.

[0007] By adopting the above technical scheme and through a reasonable ratio of PE and PA, high optical transparency of the film can be achieved. The PA layer has excellent density, chemical resistance and heat resistance, and the PE layer has excellent mechanical strength, stability and transparency. The prepared PE / PA asymmetric film has good transparency, chemical stability, heat resistance and mechanical strength, and is widely used in transparent protective layers, protective layers of optical sensors and separation functions and other fields.

[0008] The weight ratios of PA, TIE, LLD, LD, PA, and LLD are further defined so that each layer has a suitable thickness range. The coordination of the structure of each layer can reduce discontinuity and defects at the interface, thereby reducing light scattering and improving transparency. In addition, the TIE layer acts as a bonding layer to enhance the adhesion between different polymer layers, reduce interlayer peeling, and thus improve the overall transparency of the film.

[0009] Preferably, the interlayer weight ratio of PA / TIE / LLD / LLD / LD / TIE / PA / TIE / LLD is 0.128:0.067:0.076:0.076:0.221:0.067:0.106:0.067:0.192.

[0010] By adopting the above technical solution, the weight ratio of each layer of PA / TIE / LLD / LLD / LD / TIE / PA / TIE / LLD is further limited to a point value. When the weight ratio between PA / TIE / LLD / LLD / LD / TIE / PA / TIE / LLD is this numerical ratio, the obtained PE / PA asymmetric film has optimal mechanical properties, mechanical properties and transparency.

[0011] Preferably, the raw materials of the LD layer include the following raw materials in parts by weight: 60-70 parts of low-density polyethylene, 15-20 parts of modified glass fiber, 10-13 parts of modified diatomaceous earth, 5-8 parts of polytetrafluoroethylene, 5-8 parts of maleic anhydride grafted polyolefin elastomer, and 2-3 parts of disulfide phase.

[0012] By adopting the above technical scheme, low-density polyethylene has good flexibility, high impact resistance, chemical stability and good transparency, so that the LD layer is not easy to break when subjected to external force and can resist the erosion of various chemical substances. The modified glass fiber has high modulus and high strength, and can form a reinforcing skeleton in the LD matrix, so that the composite material can better disperse stress when bearing load, thereby improving tensile strength, bending strength and compressive strength; the modified glass fiber has a high hardness, which can improve the wear resistance of the LD layer and reduce material loss during friction and wear. The modified diatomaceous earth has a large number of orderly arranged micropores, high porosity, and large specific surface area. When combined with the modified glass fiber, it improves the modulus and bending strength of the LD layer, improves the mechanical properties of the system, and the microporous structure of the modified diatomaceous earth can be used as a barrier layer to improve the barrier properties of the LD material to gas and moisture.

[0013] Polytetrafluoroethylene can improve the durability, weather resistance and barrier properties of LD materials, so that they can maintain stable performance in outdoor and harsh environments, and reduce aging and degradation. Maleic anhydride grafted polyolefin elastomer acts as a compatibilizer to promote chemical bonding between different polymers, reduce phase separation, avoid the formation of opaque phase interfaces, and improve the adhesion and mechanical properties of the LD layer; maleic anhydride grafted polyolefin elastomer improves the dispersibility of other components in the LD layer, reduces the aggregation of opaque particles, thereby improving transparency, and can also optimize the refractive index of the LD layer, control the crystallinity and crystal morphology, and reduce the reflection and scattering of light at different phase interfaces, thereby improving transparency. The disulfide phase has excellent lubricating properties, significantly reduces the friction coefficient of the LD layer, reduces wear, improves the sliding properties of the material, and facilitates the subsequent processing and application of the LD layer.

[0014] Preferably, the method for preparing the modified glass fiber comprises the following steps: (1) cutting the glass fiber to a length of 1-2 mm, dispersing it in deionized water, adding a silane coupling agent, stirring at a temperature of 60-65° C. for 10-15 min, filtering, and drying to obtain pretreated glass fiber; (2) washing the straw powder with anhydrous ethanol for 2-3 times, then dispersing it in a NaOH solution and soaking it for 20-25 minutes at a soaking temperature of 70-75° C., washing it with water, filtering it, and drying it to obtain pretreated straw powder; (3) coating the surface of the pretreated glass fiber in step (1) with a modified chitosan solution, and then evenly spraying the pretreated straw powder in step (2) onto the surface of the glass fiber, and drying to obtain modified glass fiber.

[0015] By adopting the above technical solution, the glass fiber is first sheared and then mixed with the silane coupling agent. The silicon-oxygen-silicon bond formed after the silane coupling agent reacts with the surface of the glass fiber can firmly connect the glass fiber and other components, improve the bonding strength of the interface, and make the composite material have higher mechanical properties.

[0016] The NaOH solution is used to treat the straw powder, which changes the chemical properties of the straw surface and increases the reaction sites, which is beneficial to the subsequent chemical modification and improves the interface bonding between the straw powder and the matrix material, thereby improving the performance of the composite material.

[0017] The surface of the pretreated glass fiber is coated with a modified chitosan solution, and the modified chitosan forms a film on the glass fiber. Then the pretreated straw powder is evenly sprayed on the surface of the glass fiber. The straw powder can adhere to the surface of the glass fiber to improve the mechanical properties of the modified fiber. The high strength and high modulus characteristics of the glass fiber are combined with the biocompatibility of chitosan and the natural cellulose structure of the straw powder to prepare a composite material with excellent mechanical properties. The obtained composite material has good biocompatibility, corrosion resistance, flame retardancy and thermal stability.

[0018] Preferably, the mass ratio of the glass fiber, the modified chitosan solution and the pretreated straw powder is 1:0.04-0.06:0.1-0.3.

[0019] By adopting the above technical solution, the mass ratio of glass fiber, modified chitosan solution and pretreated straw powder is further limited within a certain range, the mechanical properties, stability and wear resistance of glass fiber are improved, the modified chitosan solution can coat glass fiber, form a film on the surface of glass fiber, pretreated straw powder can adhere to the surface of glass fiber, the modified chitosan solution has a certain viscosity, so that the pretreated straw powder can stably adhere to the surface of glass fiber, improve the mechanical properties of glass fiber, and subsequently apply it to PE film to enhance the mechanical properties of PE film, improve its tensile strength and modulus, and make it stronger when subjected to external force. Moreover, the addition of chitosan and glass fiber can improve the barrier properties of PE film, reduce the penetration of gas and moisture, and improve the thermal stability of PE film, so that it can still maintain good performance in high temperature environment.

[0020] Preferably, the method for preparing the modified chitosan solution comprises the following steps: dissolving chitosan in acetic acid solution, magnetically stirring at room temperature until the chitosan is completely dissolved, then adding sodium alginate and hydroxymethyl cellulose, stirring at a temperature of 80-85°C for 30-35 minutes, and standing to obtain a modified chitosan solution.

[0021] By adopting the above technical scheme, chitosan is dispersed in acetic acid solution, stirred evenly, sodium alginate and hydroxymethyl cellulose are added, electrostatic attraction occurs between the primary amino group of chitosan and the carboxyl group of sodium alginate, and sodium alginate forms a composite gel with chitosan through electrostatic action, strengthening the network structure of the material, thereby improving viscosity. Hydroxymethyl cellulose can be physically cross-linked with chitosan and sodium alginate to form a composite gel, and the hydroxyl group of hydroxymethyl cellulose can form hydrogen bonds with the amino group of chitosan to increase the viscosity of the material. The hydroxyl group of hydroxymethyl cellulose can form hydrogen bonds with the carboxylic acid group of sodium alginate, and this effect can enhance the attraction between molecules, thereby improving the viscosity of the mixture. The mixture of chitosan, sodium alginate and hydroxymethyl cellulose has a synergistic effect, which increases the stability, mechanical properties and viscosity of the system, and subsequently makes the glass fiber and straw powder bond tightly, increasing the comprehensive performance of the glass fiber.

[0022] Preferably, the method for preparing the modified diatomite comprises the following steps: (1) calcining diatomaceous earth at 300-320° C. for 50-60 min, classifying and crushing, then dispersing in a sodium oxalate solution, stirring for 16-20 min, filtering, and drying to obtain pretreated diatomaceous earth; (2) dispersing titanium dioxide in deionized water, adding fatty alcohol polyoxyethylene ether and dispersant MF, stirring evenly, filtering, and drying to obtain pretreated titanium dioxide; (3) Dispersing the pretreated diatomaceous earth in step (1) in deionized water, adding the pretreated titanium dioxide and modified starch in step (2), stirring at a temperature of 80-85° C. for 1-2 h, and drying to obtain modified diatomaceous earth.

[0023] By adopting the above technical solution, diatomite is calcined to change the particle structure and surface characteristics of diatomite, making it more loose and porous, and improving its adsorption performance, purity and stability. After sodium oxalate is mixed with diatomite, the surface properties of diatomite are changed and its adsorption capacity is improved. The addition of sodium oxalate can increase the negative charge on the surface of diatomite, making it have stronger adsorption capacity for positively charged pollutants.

[0024] Fatty alcohol polyoxyethylene ether can be adsorbed on the surface of titanium dioxide particles to form a protective film to prevent the particles from reaggregating during processing and storage, thereby enhancing the stability of the system. Dispersant MF can reduce the surface tension between titanium dioxide particles and prevent particle agglomeration, thereby improving the dispersibility of titanium dioxide in the system. The synergistic effect of dispersant MF and fatty alcohol polyoxyethylene ether can improve the processing performance of titanium dioxide in the polymer matrix, improve fluidity, make titanium dioxide easier to be evenly distributed in the matrix, and have good dispersibility.

[0025] Pretreated titanium dioxide can be loaded on the surface and pores of the pretreated diatomite structure, improving the adsorption, hiding power and air permeability of the diatomite. The modified starch has certain viscosity and film-forming properties, which can make the titanium dioxide adhere to the surface of the diatomite and improve the performance stability of the modified diatomite. The obtained diatomite has excellent mechanical properties, adsorption, hiding power and air permeability.

[0026] Preferably, the mass ratio of the diatomaceous earth, titanium dioxide and modified starch is 1:0.3-0.4:0.1-0.2.

[0027] By adopting the above technical solution, the mass ratio of diatomite, titanium dioxide and modified starch is further limited within a certain range, titanium dioxide has high hiding power and good optical properties, diatomite has a porous structure and high adsorption, titanium dioxide can be loaded on the surface and pores of diatomite, and the hiding power, optical properties, adsorption properties and air permeability of diatomite are improved. Modified starch has excellent viscosity and adsorption, so that titanium dioxide can be stably loaded in the diatomite structure, further improving the mechanical properties, stability and mechanical strength of diatomite, and subsequently improving the corresponding properties of the PE layer.

[0028] Preferably, the preparation method of the modified starch comprises the following steps: dispersing the starch in a sodium hydroxide solution, reacting at 40-45°C for 4-5h, centrifuging, pouring off the supernatant, adding water and shaking, centrifuging, filtering and drying to obtain pretreated starch, then dispersing it in deionized water, adding nano-calcium carbonate and xanthan gum, stirring at a temperature of 60-65°C, drying, and grinding to obtain modified starch.

[0029] By adopting the above technical scheme, starch is mixed with sodium hydroxide solution to obtain pretreated starch, and sodium hydroxide can cause the fracture inside starch molecules and the formation of cross-linked structure, so that starch molecules are transformed from granular structure to uniform colloidal structure, and the viscosity of pretreated starch is improved. Nano calcium carbonate can be evenly dispersed in the starch system, forming heterogeneous nucleation, improving the crystallization performance of the system, and improving its heat-resistant decomposition performance and heat-resistant deformation performance. The interaction between xanthan gum and starch molecules can change the microstructure of starch paste, form hydrogen bonds or chain entanglements, and improve the viscosity of the starch system. The mixed use of xanthan gum and nano calcium carbonate can promote the dispersion of nano calcium carbonate in the matrix, improve the stability of the system, and the viscosity of xanthan gum can prevent the agglomeration of nano calcium carbonate, ensure its uniform distribution in the matrix, thereby optimizing the performance of the material, and significantly improving the mechanical properties of the composite material, such as impact strength and flexural strength. Starch, nano calcium carbonate and xanthan gum are mixed with synergistic effect, and the modified starch obtained has good mechanical properties, viscosity, and processing properties, which helps to make the performance between diatomaceous earth and titanium dioxide in the future, and change the corresponding performance of the PE layer in the future.

[0030] On the second aspect, the present application also provides a method for preparing a highly transparent PE / PA asymmetric film, comprising the following steps: melting and plasticizing PA resin, TIE resin, LLD resin, LLD resin, LD resin, TIE resin, PA resin, TIE resin, and LLD resin in different extruders respectively, extruding the molten resin into the same die head, and evenly distributing the resins in the die head according to a certain interlayer structure, and using a nine-layer blown film equipment to blow, cool and shape, and roll up to obtain an asymmetric nine-layer co-extruded nylon film.

[0031] By adopting the above technical solution and the above preparation method, the operation is simple and the process time is short, which helps to improve the production efficiency of preparing highly transparent PE / PA asymmetric membranes. The obtained highly transparent PE / PA asymmetric membranes have good mechanical properties.

[0032] In summary, this application has the following beneficial effects: 1. In this application, a reasonable ratio of PE and PA is used to achieve high optical transparency of the film. The PA layer has excellent density, chemical resistance, and heat resistance, and the PE layer has excellent mechanical strength, stability, and transparency. The prepared PE / PA asymmetric film has good transparency, chemical stability, heat resistance, and mechanical strength.

[0033] 2. The weight ratios of PA, TIE, LLD, LD, PA, and LLD are defined in this application so that each layer has a suitable thickness range. The coordination of the structure of each layer can reduce discontinuity and defects at the interface, thereby reducing light scattering and improving transparency.

[0034] 3. In the present application, the TIE layer is used as a bonding layer, and its function is to enhance the adhesion between different polymer layers, reduce interlayer peeling, and thus improve the overall transparency of the film. DETAILED DESCRIPTION

[0035] The present application is further described in detail below with reference to the embodiments.

[0036] The raw materials used in the examples and comparative examples can all be obtained commercially.

[0037] Preparation example of modified glass fiber Preparation Example 1-1 The preparation method of modified glass fiber comprises the following steps: (1) 1.2 kg of glass fiber was cut into a length of 1-2 mm, then dispersed in 2 L of deionized water, silane coupling agent KH-550 was added, stirred at a temperature of 65° C. for 12 min, filtered, and dried to obtain pretreated glass fiber; (2) washing 0.8 kg of straw powder with anhydrous ethanol for three times, then dispersing it in 1.5 L of a 30% by mass NaOH solution and soaking it for 25 min at a soaking temperature of 75° C., washing it with water, filtering it, and drying it to obtain pretreated straw powder; (3) coating the surface of the pretreated glass fiber in step (1) with a modified chitosan solution, and then evenly spraying the pretreated straw powder in step (2) onto the surface of the glass fiber, and drying to obtain modified glass fiber.

[0038] The mass ratio of glass fiber, modified chitosan solution and pretreated straw powder is 1:0.04:0.1.

[0039] The preparation method of modified chitosan solution comprises the following steps: dissolving 1 kg chitosan in 2 L acetic acid solution with a concentration of 5%, stirring magnetically at room temperature until the chitosan is completely dissolved, then adding 0.3 kg sodium alginate and 0.1 kg hydroxymethyl cellulose, stirring at a temperature of 85° C. for 35 minutes, and standing to obtain a modified chitosan solution.

[0040] Preparation Example 1-2 The difference from Preparation Example 1-1 is that in step (2), no straw powder is added.

[0041] Preparation Example 1-3 The difference from Preparation Example 1-1 is that in step (3), no modified chitosan solution is added.

[0042] Preparation Example 1-4 The difference from Preparation Example 1-1 is that the mass ratio of glass fiber, modified chitosan solution and pretreated straw powder is 1:0.06:0.3.

[0043] Preparation Example 1-5 The difference from Preparation Example 1-1 is that the mass ratio of glass fiber, modified chitosan solution and pretreated straw powder is 1:0.01:0.6.

[0044] Preparation Example 1-6 The difference from Preparation Example 1-1 is that sodium alginate is not added in the preparation method of the modified chitosan solution.

[0045] Preparation Example 1-7 The difference from Preparation Example 1-1 is that hydroxymethyl cellulose is not added in the preparation method of the modified chitosan solution.

[0046] Preparation example of modified diatomite Preparation Example 2-1 The preparation method of modified diatomite comprises the following steps: (1) 1.8 kg of diatomaceous earth was calcined at 320° C. for 55 min, put into a jet mill classifier for classification and fine crushing, and then dispersed in 2.5 L of a 55% sodium oxalate solution, stirred for 20 min, filtered, and dried to obtain pretreated diatomaceous earth; (2) dispersing titanium dioxide in 1.2 L of deionized water, adding 0.05 kg of fatty alcohol polyoxyethylene ether and 0.04 kg of dispersant MF, stirring evenly, filtering, and drying to obtain pretreated titanium dioxide; (3) Disperse the pretreated diatomaceous earth in step (1) in 4.5 L of deionized water, add the pretreated titanium dioxide and modified starch in step (2), stir at 85° C. for 1.5 h, and dry to obtain modified diatomaceous earth.

[0047] The mass ratio of diatomaceous earth, titanium dioxide and modified starch is 1:0.3:0.2.

[0048] The preparation method of modified starch comprises the following steps: dispersing 0.9 kg of starch in 1.5 L of sodium hydroxide solution with a mass fraction of 0.8%, reacting at 45 DEG C for 5 hours, centrifuging, pouring out the supernatant, adding water and shaking, centrifuging, filtering and drying to obtain pretreated starch, then dispersing in 3 L of deionized water, adding 0.1 kg of nano calcium carbonate and 0.08 kg of xanthan gum, stirring at a temperature of 65 DEG C, drying, grinding, and obtaining modified starch.

[0049] Preparation Example 2-2 The difference from Preparation Example 2-1 is that in step (2), no titanium dioxide is added.

[0050] Preparation Example 2-3 The difference from Preparation Example 2-1 is that in step (3), no modified starch is added.

[0051] Preparation Example 2-4 The difference from Preparation Example 2-1 is that the mass ratio of diatomaceous earth, titanium dioxide and modified starch is 1:0.4:0.1.

[0052] Preparation Example 2-5 The difference from Preparation Example 2-1 is that the mass ratio of diatomaceous earth, titanium dioxide and modified starch is 1:0.1:0.5.

[0053] Preparation Example 2-6 The difference from Preparation Example 2-1 is that no nano calcium carbonate is added in the preparation method of the modified starch.

[0054] Preparation Example 2-7 The difference from Preparation Example 2-1 is that xanthan gum is not added in the preparation method of the modified starch. Example

[0055] Example 1 A highly transparent PE / PA asymmetric film with a structure of PA / TIE / LLD / LLD / LD / TIE / PA / TIE / LLD; The interlayer weight ratio of PA / TIE / LLD / LLD / LD / TIE / PA / TIE / LLD is 0.128:0.067:0.076:0.076:0.221:0.067:0.106:0.067:0.192, among which the weight of LD is 1 kg.

[0056] The preparation method of the above-mentioned highly transparent PE / PA asymmetric film comprises the following steps: 1.5kg PA resin, 0.5kg TIE resin, 1.2kg LLD resin, 1.2kg LLD resin, 1.3kg LD resin, 0.5kg TIE resin, 1.5kg PA resin, 0.5kg TIE resin, and 1.2kg LLD resin are melted and plasticized in different extruders respectively, the molten resins are extruded into the same die head, and the molten resins are evenly distributed in the die head according to a certain interlayer structure, and the asymmetric structure nine-layer co-extruded nylon film is obtained by blowing, cooling, shaping, and winding through a nine-layer film blowing equipment; wherein, the film blowing: the die head is 210°C, the film blowing is stretched 3 times in the longitudinal direction and 4 times in the transverse direction, the stretching temperature is 80°C, and the blowing ratio is 1.5.

[0057] PA resin was purchased from Dongguan Baojia Plastic Co., Ltd., TIE resin is EVA modified adhesive resin purchased from Dongguan Taotao Plastic Raw Materials Co., Ltd.; LLD resin is linear low-density polyethylene purchased from Shanghai Youcheng International Trade Co., Ltd.; LD resin is low-density polyethylene purchased from Yuyao Deyi Plastic Chemical Co., Ltd.

[0058] The interlayer film thicknesses of PA / TIE / LLD / LLD / LD / TIE / PA / TIE / LLD are: 4μm, 3μm, 4μm, 4μm, 5μm, 3μm, 4μm, 3μm, and 4μm respectively.

[0059] Example 2 A highly transparent PE / PA asymmetric film, which differs from Example 1 in that the interlayer weight ratio is 0.125:0.064:0.073:0.073:0.218:0.070:0.109:0.064:0.195.

[0060] Example 3 A highly transparent PE / PA asymmetric film, which differs from Example 1 in that the interlayer weight ratio is 0.131:0.070:0.079:0.079:0.224:0.064:0.103:0.070:0.189.

[0061] Example 4 A highly transparent PE / PA asymmetric membrane, which differs from Example 1 in that the raw materials of the LD layer, by weight, include the following raw materials: 60 kg of low-density polyethylene, 15 kg of modified glass fiber, 10 kg of modified diatomaceous earth, 5 kg of polytetrafluoroethylene, 5 kg of maleic anhydride grafted polyolefin elastomer, and 3 kg of disulfide phase.

[0062] The modified glass fiber was prepared by using Preparation Example 1-1; and the modified diatomaceous earth was prepared by using Preparation Example 2-1.

[0063] Example 5 A highly transparent PE / PA asymmetric membrane, which differs from Example 4 in that the raw materials of the LD layer, by weight, include the following raw materials: 70 kg of low-density polyethylene, 20 kg of modified glass fiber, 13 kg of modified diatomaceous earth, 8 kg of polytetrafluoroethylene, 8 kg of maleic anhydride grafted polyolefin elastomer, and 2 kg of disulfide phase.

[0064] Example 6 A highly transparent PE / PA asymmetric membrane, which is different from Example 4 in that the modified glass fiber is prepared using Preparation Example 1-2.

[0065] Example 7 A highly transparent PE / PA asymmetric membrane, which is different from Example 4 in that the modified glass fiber is prepared using Preparation Examples 1-3.

[0066] Example 8 A highly transparent PE / PA asymmetric membrane, which is different from Example 4 in that the modified glass fiber is prepared using Preparation Examples 1-4.

[0067] Example 9 A highly transparent PE / PA asymmetric membrane, which is different from Example 4 in that the modified glass fiber is prepared using Preparation Examples 1-5.

[0068] Example 10 A highly transparent PE / PA asymmetric membrane, which is different from Example 4 in that the modified glass fiber is prepared using Preparation Examples 1-6.

[0069] Embodiment 11 A highly transparent PE / PA asymmetric membrane, which is different from Example 4 in that the modified glass fiber is prepared using Preparation Examples 1-7.

[0070] Example 12 A highly transparent PE / PA asymmetric membrane, which is different from Example 4 in that the modified diatomaceous earth is prepared using Preparation Example 2-2.

[0071] Embodiment 13 A highly transparent PE / PA asymmetric membrane, which is different from Example 4 in that the modified diatomaceous earth is prepared using Preparation Example 2-3.

[0072] Embodiment 14 A highly transparent PE / PA asymmetric membrane, which is different from Example 4 in that the modified diatomaceous earth is prepared using Preparation Examples 2-4.

[0073] Embodiment 15 A highly transparent PE / PA asymmetric membrane, which is different from Example 4 in that the modified diatomaceous earth is prepared using Preparation Examples 2-5.

[0074] Example 16 A highly transparent PE / PA asymmetric membrane, which is different from Example 4 in that the modified diatomaceous earth is prepared using Preparation Examples 2-6.

[0075] Embodiment 17 A highly transparent PE / PA asymmetric membrane, which is different from Example 4 in that the modified diatomaceous earth is prepared using Preparation Examples 2-7.

[0076] Comparative Example Comparative Example 1 A highly transparent PE / PA asymmetric film, which differs from Example 1 in that the interlayer weight ratio is 0.115:0.053:0.071:0.071:0.202:0.053:0.100:0.053:0.180.

[0077] Comparative Example 2 A highly transparent PE / PA asymmetric film, which differs from Example 1 in that the interlayer weight ratio is 0.138:0.085:0.082:0.082:0.229:0.085:0.111:0.085:0.199.

[0078] Performance testing The high-transparency PE / PA asymmetric films prepared in Examples 1-17 and Comparative Examples 1-2 were subjected to performance tests. The tensile strength and elongation at break of the films were tested according to GB / T1040.3-2006; the film puncture force test and dart impact test were tested according to GB / T9639.1-2008 and GB / T10004-2008; the average mixed gas permeability (the main components of the mixed gas are oxygen and nitrogen) of the films was tested according to GB / T1038-2000 (unit: 10 μm (g / m 2 ·24h)); UV spectrophotometer (UV-2600I, SHIMADZU Japan) was used to test the absorption performance of the film in the visible light region, with a measuring wavelength of 600nm. The test results are shown in Table 1.

[0079] Table 1 Test data of embodiments and comparative examples As can be seen from Table 1, the highly transparent PE / PA asymmetric films prepared in Examples 1-3 of the present application have good mechanical properties, barrier properties, transparency and mechanical strength, wherein the longitudinal tensile strength of Example 1 reaches 42.5MPa, the transverse tensile strength reaches 34.2MPa, the longitudinal elongation at break is 397.2%, the transverse elongation at break is 521.3%, the film puncture force is 1.781N, the dart impact mass is 689g, the mixed gas permeability is 312.5±2.3 10μm (g / m2·24h), and the light transmittance is 92%. It shows that the prepared highly transparent PE / PA asymmetric film has good mechanical properties and mechanical strength, and the coordination of each layer structure can reduce the discontinuity and defects at the interface, thereby reducing light scattering and improving transparency, and the PE / PA asymmetric film has good barrier properties, which can effectively block oxygen, nitrogen, etc. in the environment.

[0080] The raw materials of the PE layer of Examples 4-5 are homemade by the present application. Compared with Example 1, the obtained PE / PA asymmetric membrane has better mechanical properties, barrier properties and transparency, indicating that the modified glass fiber and modified diatomaceous earth used in the present application improve the mechanical properties of the PE layer, but still maintain a high transparency.

[0081] In the preparation method of the modified glass fiber of Examples 6-7, straw powder and modified chitosan solution are not added respectively. In Examples 8-9, the mass ratio of glass fiber, modified chitosan solution and pretreated straw powder is changed. As can be seen from Table 1, the performance test results of tensile strength, elongation at break, film puncture force, dart impact mass and mixed gas permeability of Examples 6-7 are significantly worse than those of Examples 4-5. The performance test results of tensile strength, elongation at break, film puncture force, dart impact mass and mixed gas permeability of Example 9 are better than those of Examples 5-7, but worse than those of Examples 4-5 and Example 8, indicating that the modified chitosan solution can coat the glass fiber, the pretreated straw powder can adhere to the surface of the glass fiber, and the modified chitosan solution enables the pretreated straw powder to stably adhere to the surface of the glass fiber, thereby improving the mechanical properties of the glass fiber, and is subsequently applied to the PE film to enhance the mechanical properties of the PE film. Moreover, the addition of chitosan and glass fiber can improve the barrier properties of the PE film, reduce the penetration of gas and moisture, and improve the barrier properties of the PE film.

[0082] In the preparation method of the modified chitosan solution of Examples 10-11, sodium alginate and hydroxymethyl cellulose are not added respectively. As can be seen from Table 1, the performance test results of tensile strength, elongation at break, film puncture force, dart impact mass, and mixed gas permeability of Examples 10-11 are significantly worse than those of Examples 4-5, but better than those of Example 7, indicating that the mixture of chitosan, sodium alginate and hydroxymethyl cellulose has a synergistic effect, which increases the stability, mechanical properties and viscosity of the system, and subsequently makes the glass fiber and straw powder bond tightly, thereby increasing the comprehensive performance of the glass fiber.

[0083] In the preparation method of modified diatomite in Examples 12-13, titanium dioxide and modified starch are not added respectively, and the mass ratio of diatomite, titanium dioxide and modified starch is changed in Examples 14-15. As can be seen from Table 1, the performance test results of tensile strength, elongation at break, film puncture force, dart impact mass and mixed gas permeability of Examples 12-13 are significantly worse than those of Examples 4-5, and the performance test results of tensile strength, elongation at break, film puncture force, dart impact mass and mixed gas permeability of Example 15 are better than those of Examples 12-13, but worse than those of Examples 4-5 and Example 14, indicating that titanium dioxide can be loaded on the surface and pores of diatomite, thereby improving the hiding power, barrier properties, adsorption properties and air permeability of diatomite. The modified starch has excellent viscosity and adsorption, so that titanium dioxide can be stably loaded in the diatomite structure, further improving the mechanical properties, stability and mechanical strength of diatomite, and subsequently improving the corresponding properties of the PE layer.

[0084] In the preparation method of the modified starch of Examples 16-17, nano calcium carbonate and xanthan gum are not added respectively. As can be seen from Table 1, the performance test results of tensile strength, elongation at break, film puncture force, dart impact mass and mixed gas permeability of Examples 16-17 are better than those of Example 13, but worse than those of Examples 4-5, indicating that the mixture of starch, nano calcium carbonate and xanthan gum has a synergistic effect, and the obtained modified starch has good mechanical properties, viscosity and processing properties, which in turn helps to subsequently improve the performance between diatomaceous earth and titanium dioxide, and subsequently change the corresponding properties of the PE layer.

[0085] Comparative Examples 1-2 respectively change the interlayer weight ratio of PA / TIE / LLD / LLD / LD / TIE / PE / TIE / LL+LD. Compared with Examples 1-3, the performance test results of the tensile strength, elongation at break, film puncture force, dart impact mass, and mixed gas permeability of the film are significantly worse than those of Examples 1-3, indicating that the weight ratio between each film layer specified in the present application has a great influence on the comprehensive performance of the film. The appropriate weight ratio of each film layer is set so that the layers have a suitable thickness range. The coordination of the structure of each layer can reduce the discontinuity and defects at the interface, thereby reducing light scattering and improving transparency and mechanical properties.

[0086] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A highly transparent PE / PA asymmetric film, characterized in that: The structure is PA / TIE / LLD / LLD / LD / TIE / PA / TIE / LLD, and the weight ratio between layers is 0.125-0.131:0.064-0.070:0.073-0.079:0.073-0.079:0.218-0.224:0.064-0.070:0.103-0.109:0.064-0.070:0.189-0.

195.

2. A highly transparent PE / PA asymmetric film according to claim 1, characterized in that: The interlayer weight ratio of PA / TIE / LLD / LLD / LD / TIE / PA / TIE / LLD is 0.128:0.067:0.076:0.076:0.221:0.067:0.106:0.067:0.

192.

3. A highly transparent PE / PA asymmetric film according to claim 1, characterized in that: The raw materials of the LD layer include the following raw materials in parts by weight: 60-70 parts of low-density polyethylene, 15-20 parts of modified glass fiber, 10-13 parts of modified diatomaceous earth, 5-8 parts of polytetrafluoroethylene, 5-8 parts of maleic anhydride grafted polyolefin elastomer, and 2-3 parts of disulfide phase.

4. A highly transparent PE / PA asymmetric film according to claim 3, characterized in that: The method for preparing the modified glass fiber comprises the following steps: (1) Cut the glass fiber to a length of 1-2 mm, then disperse it in deionized water, add a silane coupling agent, stir it at a temperature of 60-65°C for 10-15 minutes, filter it, and dry it to obtain pretreated glass fiber; (2) washing the straw powder with anhydrous ethanol for 2-3 times, then dispersing it in a NaOH solution and soaking it for 20-25 minutes at a soaking temperature of 70-75°C, washing it with water, filtering it, and drying it to obtain pretreated straw powder; (3) coating the surface of the pretreated glass fiber in step (1) with a modified chitosan solution, and then spraying the pretreated straw powder in step (2) evenly onto the surface of the glass fiber, and drying to obtain modified glass fiber.

5. A highly transparent PE / PA asymmetric film according to claim 4, characterized in that: The mass ratio of the glass fiber, the modified chitosan solution and the pretreated straw powder is 1:0.04-0.06:0.1-0.

3.

6. A highly transparent PE / PA asymmetric film according to claim 4, characterized in that: The preparation method of the modified chitosan solution comprises the following steps: dissolving chitosan in acetic acid solution, magnetically stirring at room temperature until the chitosan is completely dissolved, then adding sodium alginate and hydroxymethyl cellulose, stirring at a temperature of 80-85° C. for 30-35 minutes, and standing to obtain the modified chitosan solution.

7. The highly transparent PE / PA asymmetric film according to claim 1, characterized in that: The preparation method of the modified diatomite comprises the following steps: (1) calcining diatomaceous earth at 300-320° C. for 50-60 min, classifying and crushing, and then dispersing in a sodium oxalate solution, stirring for 16-20 min, filtering, and drying to obtain pretreated diatomaceous earth; (2) dispersing titanium dioxide in deionized water, adding fatty alcohol polyoxyethylene ether and dispersant MF, stirring evenly, filtering, and drying to obtain pretreated titanium dioxide; (3) Dispersing the pretreated diatomaceous earth in step (1) in deionized water, adding the pretreated titanium dioxide and modified starch in step (2), stirring at a temperature of 80-85° C. for 1-2 h, and drying to obtain modified diatomaceous earth.

8. A highly transparent PE / PA asymmetric film according to claim 7, characterized in that: The mass ratio of the diatomaceous earth, titanium dioxide and modified starch is 1:0.3-0.4:0.1-0.

2.

9. The highly transparent PE / PA asymmetric film according to claim 7, characterized in that: The preparation method of the modified starch comprises the following steps: dispersing starch in a sodium hydroxide solution, reacting at 40-45°C for 4-5h, centrifuging, discarding the supernatant, adding water, shaking and centrifuging, filtering and drying to obtain pretreated starch, then dispersing the starch in deionized water, adding nano calcium carbonate and xanthan gum, stirring at a temperature of 60-65°C, drying, and grinding to obtain the modified starch.

10. The method for preparing a highly transparent PE / PA asymmetric film according to claim 1, characterized in that: The method comprises the following steps: melting and plasticizing PA resin, TIE resin, LLD resin, LLD resin, LD resin, TIE resin, PA resin, TIE resin and LLD resin in different extruders respectively, extruding the melted resin into the same die head, uniformly distributing the resins in the die head according to a certain interlayer structure, and blowing, cooling and shaping, and winding the resins through a nine-layer film blowing device to obtain an asymmetric nine-layer co-extruded nylon film.

Citation Information

Patent Citations

  • Asymmetric seven-layer co-extruded nylon membrane

    CN104669737A

  • Production method of high-barrier nylon PE co-extruded film

    CN112776442A

  • Acid and alkali resistant protective film and preparation method thereof

    CN118496633A

  • Waterproof film for washing machine and preparation process

    CN118667250A